Bioelectricity generation using human neuronal-like cells in single chamber biofuel cells - Arslan, Belkis Atasever; Akdogan, Erhan; Cebeci, Fevzi Cakmak; Catal, Tunc (ELSEVIER SCI LTD, 2020)
Bioelectricity production was achieved using human neuronal-like cells called SH-SY5Y cell line in single-chamber air-cathode fuel cells. Dulbecco's Modified Eagle's medium was used as the carbon source. SH-SY5Y cells grown on carbon cloth were used as anode in the experiments. The voltage was 96 mV using 980 Omega external resistance. Voltage levels decreased when the medium was replaced with medium containing 4.5 g L-1 of glucose. Maximum power density, current density and Coulombic efficiency were measured as 12 mW m(-2), 0.013 mA cm(-2) and 15%, respectively. Anode biofllm was examined using a multipotentiostat, and cyclic voltammetry results showed redox activity. The output of the fuel cell was connected to a circuit to power LEDs, by using the circuit as a voltage-controlled current source. The results demonstrated for the first time that human neuronal-like cells can generate bioelectricity in a fuel cell to power LEDs. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Biofuel cell; Electricity; LED; Stem cell; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology